2021
DOI: 10.1002/admt.202100777
|View full text |Cite
|
Sign up to set email alerts
|

Smart Refreshable Braille Display Device Based on Magneto‐Resistive Composite with Triple Shape Memory

Abstract: Braille devices made from stimuli‐active polymers have provided a new approach for obtaining information on Braille text. However, it is still essential to find a more convenient and effective method to develop multifunctional Braille devices with shape memory effects to broaden their applications. Here, a novel smart refreshable Braille display based on triple‐shape memory and magnetoresistive composite is developed with the advantages of simple fabrication, multifunctionality, and harmlessness for blind peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The mechanical performance of LM/ PBSE is also compared with some common elastomer composites, such as PDMS elastomer, 31,32 double-network elastomer, 33 PBSG base composite, 34 sponge elastomer, 35 LM/ gel, 36 and LM/PCL. 37 It is demonstrated that the LM/PBSE fabricated in this work achieves a higher fracture strain while maintaining good flexibility (Figure 2h). The strain−stress hysteresis curve of the LM/PBSE with different LM components is also evaluated through a series of uniaxial cycling loadings from ε = 0.1 to 0.5 (SI Figure S7).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The mechanical performance of LM/ PBSE is also compared with some common elastomer composites, such as PDMS elastomer, 31,32 double-network elastomer, 33 PBSG base composite, 34 sponge elastomer, 35 LM/ gel, 36 and LM/PCL. 37 It is demonstrated that the LM/PBSE fabricated in this work achieves a higher fracture strain while maintaining good flexibility (Figure 2h). The strain−stress hysteresis curve of the LM/PBSE with different LM components is also evaluated through a series of uniaxial cycling loadings from ε = 0.1 to 0.5 (SI Figure S7).…”
Section: Resultsmentioning
confidence: 68%
“…With the increment of Φ LM , more regions in the LM/PBSE participates in the solid–liquid coupling effect during the tensile process, resulting in a positive correlation between the ε f and Φ LM . The mechanical performance of LM/PBSE is also compared with some common elastomer composites, such as PDMS elastomer, , double-network elastomer, PBSG base composite, sponge elastomer, LM/gel, and LM/PCL . It is demonstrated that the LM/PBSE fabricated in this work achieves a higher fracture strain while maintaining good flexibility (Figure h).…”
Section: Results and Discussionmentioning
confidence: 88%
“…The blind cannot read texts as the normal because of impaired vision. Therefore, the Braille text was created, a kind of text specially designed for blind people, with each Braille letter consisting of six dots in three rows and two columns. , Blind people rely on the tactility of their fingers to read Braille, tactility is driven by skin tribology, the fundamental interaction of skin and a counter surface under contact and sliding . Potentially, the SMRM surface with precisely controllable friction and morphology properties can be utilized for designing refreshable Braille devices.…”
Section: Resultsmentioning
confidence: 99%
“…SMPs have attracted considerable interest from researchers, promoting the rapid development of smart devices and soft robotics. For example, a smart braille display based on shape-memory polymer and magneto-resistive composite has recently been developed for visually impaired people. The device can potentially be used as a portable and refreshable Braille e-book . A thermoplastic high strain shape-memory polynorbornene and a photodriven reversible shape-memory polymer are attractive options for soft machines.…”
Section: Introductionmentioning
confidence: 99%
“…The device can potentially be used as a portable and refreshable Braille e-book. 8 A thermoplastic high strain shape-memory polynorbornene 9 and a photodriven reversible shape-memory polymer 10 are attractive options for soft machines.…”
Section: ■ Introductionmentioning
confidence: 99%